To solve the expression \(3^7 \times 3^{-9}\) using the properties of integer exponents, we will start by applying the Product of Powers Property, which states that when multiplying two expressions with the same base, we add the exponents:
\[ 3^7 \times 3^{-9} = 3^{7 + (-9)} = 3^{7 - 9} = 3^{-2} \]
Next, we need to convert the expression \(3^{-2}\) to use only positive exponents. We can do this by using the property that \(a^{-n} = \frac{1}{a^n}\):
\[ 3^{-2} = \frac{1}{3^2} \]
Now, we compute \(3^2\):
\[ 3^2 = 9 \]
Thus, we can rewrite \(3^{-2}\) as:
\[ 3^{-2} = \frac{1}{9} \]
Consequently, the equivalent expression for \(3^7 \times 3^{-9}\) with only positive exponents is:
\[ \boxed{\frac{1}{9}} \]